WRIT 100: Writing in the Age of Digital Surveillance - Walsh, Brandon (Brandon Walsh, 2018)
Syllabus for an introductory writing course for first-year students based around a particular topic. Concentrated work in composition with readings in which students write at least four revised essays in addition to completing several exercises emphasizing writing as a process. Stress on active reading, argumentation, the appropriate presentation of evidence, various methods of critical analysis, and clarity of style. In this course, we examine the legal, social, and economic pressures regularly exercised on us by various groups, not all of them benign, as we live our digital lives. In particular, we explore writing as a means of taking back control in a world that is increasingly surveilled and policed. How can we become not only responsible digital consumers but also active contributors to publicly unfolding humanist pursuits on the Internet? What happens when Big Brother stops watching and starts reading? A variety of sources, journalistic, public, and academic frame course discussions, and we also explore a few digital humanities methods for critically examining digital information. In addition to extensive practice with critical writing, the course also offers an option for pitching and crafting a piece of writing for a public venue.
Originally shared on my blog along with other syllabi - http://walshbr.com/pedagogy/
Original submission date: 2023-05-19T15:53:50Z
Keywords: Digital Humanities; Teaching; Composition; Writing; Pedagogy; Composition